2016
DOI: 10.1039/c6tb01730d
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel berberine-mediated mitochondria-targeting nano-platform for drug-resistant cancer therapy

Abstract: A novel berberine-mediated mitochondria-targeting nano-platform was constructed to inhibit tumor growth and bypass the multi-drug resistance problem by targeting doxorubicin to mitochondria of tumor cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…In this regard, increasing evidence has demonstrated that PDT, a two-stage treatment that combines light energy with a drug (photosensitizer), is significantly effective against different types of cancers [34], including malignant brain tumors [8,9,35,36]. Importantly, in the search for novel photosensitizing agents, the natural plant-derived alkaloid BBR has demonstrated a broad spectrum of efficacy [37][38][39] as well as in conjunction with PDT anticancer schemes [19].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, increasing evidence has demonstrated that PDT, a two-stage treatment that combines light energy with a drug (photosensitizer), is significantly effective against different types of cancers [34], including malignant brain tumors [8,9,35,36]. Importantly, in the search for novel photosensitizing agents, the natural plant-derived alkaloid BBR has demonstrated a broad spectrum of efficacy [37][38][39] as well as in conjunction with PDT anticancer schemes [19].…”
Section: Discussionmentioning
confidence: 99%
“…Different liposomal vehicles such as positively charged liposomes containing phosphatidyl ethanolamine (PE), cholesterol, stearylamine and lipophilic cationic drug/molecule, TPP modified liposomes loaded with chlorin e6 (Ce6) and IR780 iodide, stearyl TPP-modified liposomal cargo, TPPpolyethylene glycol (PEG)-PE-modified liposomal cargo, TPP-cerosomes (Si-O-Si)-liposomal drug, PEGylated liposomes conjoined with 9-C16 berberine and folate have been utilized to treat against diseases for mitochondrial deliveries. 6,[122][123][124][125][126][127][128] Liposomal MITO-Porter containing mitochondrial fusogenic lipid envelops modified with R8, dual function (DF) MITO-Porter with mitochondrial signal peptide, stearyl modified S2 peptide decorated to DF-MITO-Porter, and R8/GALA modified MITO-Porter have been used to release cargos and target mitochondrial matrix through membrane fusion endocytic mechanism. 86,[129][130][131][132][133] Besides nucleic acids, coenzyme Q10-MITO-Porter also have been treated for mitochondrial delivery against ischemic/reperfusion injury.…”
Section: Liposomesmentioning
confidence: 99%
“…It is well-known that mitochondria also contain DNA (mtDNA), and these double-stranded circular DNA molecules take charge of the synthesis of tens of proteins . Thus, mitochondria should be another critical target for chemotherapy, and delivering DNA toxins into mitochondria is another wise choice toward enhanced chemotherapy. , …”
Section: Mitochondria-targeted Therapymentioning
confidence: 99%